Culture-Independent Quantitative PCR Detected Mobilized Colistin Resistance Genes (mcr-1, mcr-2, mcr-3, mcr-4, and mcr-5) in Chicken Gut Contents in Bangladesh - Mamun Al Asad; Md Sarower Hossen Shuvo; Shomaia Yasmin Mitu; Sumia; Md Asief Hossain Zihadi; Ayasha Siddique Shanta; Nahidul Islam; Shamsun Nahar; Brian Godman; Salequl Islam (Sci)
Inappropriate antimicrobial use in food animal farming propels antimicrobial resistance (AMR) that affects all health domains. Colistin is a ‘Reserve’ antibiotic for human treatment to be conserved for multidrug-resistant pathogens; however, it is being used as an animal growth promoter in many developing countries. The evolution of mobilized colistin resistance (mcr) gene-mediated colistin resistance has been reported to be associated with rampant colistin use. This study investigated the current variants of the mcr gene in chicken gut contents in Bangladesh. A cross-sectional study was designed to assess the mcr-1 to mcr-5 genes in 80 fresh poultry droppings from commercial poultry farms and 40 poultry droppings from household farms. DNA was extracted from each poultry dropping using commercial kits (Qiagen GmbH, Hilden, Germany). Real-time quantitative polymerase chain reaction (RT-qPCR) was employed using the qTOWER3 thermal cycler (Analytik Jena GmbH, Jena, Germany) to analyze the mcr gene variants in the extracted DNA. This study observed that 47.5% (57/120) of the samples exhibited the presence of at least one mcr gene out of the five variants investigated. The individual detection rates of the mcr-1, mcr-2, mcr-3, mcr-4, and mcr-5 genes were 42.5% (51/120), 2.5% (3/120), 1.7% (2/120), 5% (6/120), and 9.2% (11/120), respectively. The co-carriage of two or more genes was found in over 10% (10/57) of the samples. The triple occurrence of mcr genes was identified in three samples with the combination of mcr-1+mcr-2+mcr-4, mcr-1+mcr-3+mcr-5, and mcr-1+mcr-4+mcr-5. Overall, a significantly higher number of mcr genes were identified in the commercial farm chicken droppings compared to the household chicken droppings (p = 0.007). The existence of mcr genes in poultry feces in Bangladesh emphasizes the importance of proper poultry waste disposal and good hygiene practices in poultry livestock and its value chain. The potential impact of environmental ARGs should be considered in national and global policy documents. An integrated and combined approach to the One Health concept should be applied in all domains to understand and control the environment’s role in the evolution and transmission of AMR.